Safety of AADC Gene Therapy for Moderately Advanced Parkinson Disease: Three-Year Outcomes From the PD-1101 Trial. (4th January 2022) - Christine, Chadwick W.; Richardson, R. Mark; Van Laar, Amber D.; Thompson, Marin E.; Fine, Elisabeth M.; Khwaja, Omar S.; Li, Chunming; Liang, Grace S.; Meier, Andreas; Roberts, Eiry W.; Pfau, Madeline L.; Rodman, Josh R.; et al.
Abstract : Background and Objectives: To report final, 36-month safety and clinical outcomes from the PD-1101 trial of NBIb-1817 (VY-AADC01) in participants with moderately advanced Parkinson disease (PD) and motor fluctuations. Methods: PD-1101 was a phase 1b, open-label, dose escalation trial of VY-AADC01, an experimental AAV2 gene therapy encoding the human aromatic l -amino acid decarboxylase (AADC) enzyme. VY-AADC01 was delivered via bilateral, intraoperative MRI-guided putaminal infusions to 3 cohorts (n = 5 participants per cohort): cohort 1, ≤7.5 × 10 11 vector genomes (vg); cohort 2, ≤1.5 × 10 12 vg; cohort 3, ≤4.7 × 10 12 vg. Results: No serious adverse events (SAEs) attributed to VY-AADC01 were reported. All 4 non-vector–related SAEs (atrial fibrillation and pulmonary embolism in 1 participant and 2 events of small bowel obstruction in another participant) resolved. Requirements for PD medications were reduced by 21%–30% in the 2 highest dose cohorts at 36 months. Standard measures of motor function (PD diary, Unified Parkinson's Disease Rating Scale III "off"-medication and "on"-medication scores), global impressions of improvement (Clinical Global Impression of Improvement, Patient Global Impression of Improvement), and quality of life (39-item Parkinson's Disease Questionnaire) were stable or improved compared with baseline at 12, 24, and 36 months following VY-AADC01 administration across cohorts. Discussions: VY-AADC01 and the surgical administration procedure were well-tolerated and resulted in stable or improved motor function and quality of life across cohorts, as well as reduced PD medication requirements in cohorts 2 and 3 over 3 years. Trial Registration Information: NCT01973543. Classification of Evidence: This study provides Class IV evidence that, in patients with moderately advanced PD and motor fluctuations, putaminal infusion of VY-AADC01 is well tolerated and may improve motor function.